2012
DOI: 10.4236/aim.2012.24054
|View full text |Cite
|
Sign up to set email alerts
|

IFN-<i>γ</i>-, IL-4-, IL-17-, PD-1-Expressing T Cells and B Cells in Peripheral Blood from Tuberculosis Patients

Abstract: Although the efficacy of tuberculosis (TB) vaccines is tightly linked to cell-mediated immunity, some functions of T and B cells in TB patients remain unclear. To address how Mycobacterium tuberculosis infection inhibits T effector responses, we assessed the proportions of T cell subsets and B cells in peripheral blood from pulmonary TB (PTB) patients, pleural TB (PLTB) patients, and healthy subjects (HS, who showed purified protein derivative (PPD)-positive reactions) with flow cytometry. Compared to HS, PTB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Transcriptional and clinical analyses of healthy adolescents in South Africa revealed an association between inhibited Th17 responses and TB development (100). However, comparison of Th17/IL-17 levels in LTBI subjects and TB patients yielded inconsistent results: some studies reported heightened Th17/IL-17 levels in LTBI subjects (101–103), others demonstrated increased Th17/IL17 in TB patients (104107), some did not reveal differences between LTBI and TB groups (108) or found extremely low frequencies of Mtb -specific Th17 in both groups (109, 110). In our study, Mtb -specific Th17 were rare in the blood, but readily identifiable in the lungs of TB patients (110).…”
Section: Th17 Lymphocytesmentioning
confidence: 99%
“…Transcriptional and clinical analyses of healthy adolescents in South Africa revealed an association between inhibited Th17 responses and TB development (100). However, comparison of Th17/IL-17 levels in LTBI subjects and TB patients yielded inconsistent results: some studies reported heightened Th17/IL-17 levels in LTBI subjects (101–103), others demonstrated increased Th17/IL17 in TB patients (104107), some did not reveal differences between LTBI and TB groups (108) or found extremely low frequencies of Mtb -specific Th17 in both groups (109, 110). In our study, Mtb -specific Th17 were rare in the blood, but readily identifiable in the lungs of TB patients (110).…”
Section: Th17 Lymphocytesmentioning
confidence: 99%